Justice, politics and the social usefulness of news. (April 2016) - Konkes, Claire; Lester, Libby
In 2009 in Hobart, Australia, a 12-year-old ward of the state was advertised in a metropolitan newspaper as an 18-year-old prostitute. The decision to prosecute only one of the 100-plus men alleged to have paid her for sex made national headlines and gave rise to allegations of a conspiracy involving the highest levels of government and the judiciary. It also resulted in reform of the state's laws relating to the 'mistake as to age' defence. This paper examines news coverage of the institutional responses to this criminal matter in order to theoretically understand the relationship between contemporary journalistic representations of crime and politicised controversy about social problems such as child sexual exploitation. Drawing on an analysis of problem framing in news coverage and interviews with journalists and their sources, it investigates how the news value of the story was identified and seeks to identify the point at which news coverage tipped beyond social usefulness towards public outrage and conspiracy.